The effect of forest honey solution on the plaque and gingivitis index in adolescent: Pengaruh larutan madu hutan terhadap indeks plak dan gingivitis pada remaja - Thalissa Miranda Savitri; Linda Sari Sembiring; Vinna Kurniawati Sugiaman (Makassar Dental Journal, 2022)
Introduction: Plaque is the main factor that causes dental and oral health problems, one of which is gingivitis. Gingivitis is an inflammation of the gingival tissue and is often found in children, adolescents, and adults. The peak of the highest prevalence of gingivitis occurs in adolescence (90%). Maintaining dental and oral hygiene can be done mechanically by brushing your teeth, but mechanical action will be more effective if combined with chemical action, namely gargling. Forest honey solution is a natural liquid produced by honey bees and is beneficial for dental and oral problems. So, the purpose of this study was to determine the effect of gargling a solution of forest honey on plaque index and gingivitis in the oral cavity of adolescents. The research uses a literature studymethod by reviewing nationally published journals. The results showed that forest honey has four factors such as organic compounds, osmotic pressure, hydrogen peroxide, and pH. Forest honey are antibacterial and antioxi-dant so that it helps reduce pathogenic bacteria in the oral cavity. It is concluded that gargling a solution of forest honey is effect-tive in reducing plaque and gingivitis index scores in the oral cavity of adolescents.